2018
DOI: 10.1002/14651858.cd009728.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, diet and other behavioural interventions for improving cognition and school achievement in children and adolescents with obesity or overweight

Abstract: Background The global prevalence of childhood and adolescent obesity is high. Lifestyle changes towards a healthy diet, increased physical activity and reduced sedentary activities are recommended to prevent and treat obesity. Evidence suggests that changing these health behaviours can benefit cognitive function and school achievement in children and adolescents in general. There are various theoretical mechanisms that suggest that children and adolescents with excessive body fat may benefit parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 213 publications
(412 reference statements)
1
111
0
15
Order By: Relevance
“…Firstly, MEDLINE, Embase, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL, and Education Resources Information Center (ERIC) electronic databases were searched. Search terms to identify scaled‐up interventions were developed on the basis of terminology used in reviews by Milat et al Reis et al and Ben Charif et al and combined with published search filters for physical activity/sedentary behaviour, nutrition, and obesity . Search terms are described in detail in Supplement File S1.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, MEDLINE, Embase, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL, and Education Resources Information Center (ERIC) electronic databases were searched. Search terms to identify scaled‐up interventions were developed on the basis of terminology used in reviews by Milat et al Reis et al and Ben Charif et al and combined with published search filters for physical activity/sedentary behaviour, nutrition, and obesity . Search terms are described in detail in Supplement File S1.…”
Section: Methodsmentioning
confidence: 99%
“…25 We adopted this approach in accordance with a previous review instead of including any non-randomized trial. 26 AVGs were defined as any computer game using interaction between body movements and specific feedback and goals. Therefore, interventions which included consoles, such as the Nintendo Wii, Playstation (Sony Computer Entertainment Inc), and Kinect TM for Microsoft's Xbox 360TM (Microsoft Inc), and game controllers, such as GameCycle (Three Rivers Holdings) and Sony EyeToyVR (Sony Computer Entertainment Inc), were considered eligible.…”
Section: Study Selectionmentioning
confidence: 99%
“…The research of Kutlík and Čelko (2013) has shown a statistically significant impact of physical activity on the cognitive functions of children in testing that was targeted on memory, attention and executive functions. Martin et al (2018) have also reported reliable evidence for improving cognitive executive function by physical activity-only interventions. We can assume that the reason for such findings is that executive functions, which are also cognitive functions, have been found to be more sensitive to physical activity than other types of cognitive functions (Best, 2010).…”
Section: Resultsmentioning
confidence: 92%